(untitled) (Research, Society and Development, 2021)
Adequate nutrition is one of the determining factors for good nutrition, quality of life and improved physical performance. The search for healthy and adequate food is among the priorities of those seeking muscle hypertrophy. In this sense, the present study aims to verify the importance of nutrition in hypertrophy, clarifying how to obtain an improvement in musculature and in body mass gain through the practice of physical exercises associated with good nutrition. The work consists of a bibliographical research, which brought data on the importance of nutrition and its correlation with hypertrophy training. As a result, he presented some usual diets; food supplements such as Whey protein, creatine and glutamine, used to enhance performance in training and adequate nutrition for hypertrophy. As a highlight, carbohydrates and proteins are highlighted as the main food components, as well as hydration is considered an important factor in the process. It also showed that the amount of energy provided by food depends on the intensity, duration and chronicity of the training, with no standard that can be adopted by everyone. Therefore, professional monitoring is necessary in order to predict the nutritional needs of each person, based on their desired goals, thus promoting not only hypertrophy, but also maintenance and prevention of health.